In-depth LC-MS and in-vitro studies of a triterpenoid saponin capilliposide-A metabolism modulation in gut microbiota of mice - Zhao, Huan; Hu, Xueli; Guan, Shenghong; Cai, Jinhong; Li, Xiaohan; Fang, Jiaxi; Lin, Bo; Zhu, Wei; Tian, Jingkui; Jin, Juan; He, Qiang; Zhang, Xiaoyong (Frontiers in Pharmacology, 2024)
The impact of the gut microbiome on human health and conditions such as cardiovascular disease and colitis has been widely reported. Not only that, but gut microbes also have the potential to become a new direction for drug targets. Some herbal ingredients can reshape the composition of the gut microbiome as well as its metabolites. At the same time, the gut microbiota can also affect drug metabolism.Saponins have the functions of immunomodulatory, antioxidant and anticancer.However, due to its low bioavailability and unclear material basis, its application is limited. A large number of studies have reported that saponins are biotransformed under the action of intestinal microorganisms to improve drug efficacy and bioavailability. Capilliposide A is a triterpenoid saponin, which is derived from Lysimachia capillipes Hemsl..CPS-A has anti-inflammatory pharmacological activity, but the substance basis in vivo is unknown at present, so studies on the interaction between intestinal microorganisms and CPS-A may clarify the pharmacodynamic substance basis of CPS-A. Therefore, in this study, two types of animals (normal mice and colitis mice) were applied to investigate the metabolic process of CPS-A mediated by intestinal microbes and the intervention effect of CPS-A on intestinal microbial-derived metabolites based on LC-MS. The results showed that CPS-A was metabolized into the corresponding product by deglycosylation, dehydration and methylation under the action of intestinal flora. At the same time, CPS-A has different effects on the metabolites of intestinal flora in different species of mice.